The political economy of global warming - Weston, Delys E. (Curtin University, 2012)
The science is unequivocal: the Earth’s biosphere is approaching global warming tipping points which, if passed, will become irreversible, taking the planet on a trajectory to a new geological era, unsuitable for human life. The scale and timing of irreversible tipping points being passed is not definitively known. Unless however, an urgent and radical change in the direction of human activities occurs, certainly within less than a decade, wide scale catastrophe is certain. How can we stop this?There has been an absence of critically informed debate about whether the current solutions proposed by international institutions (market, technical or biofuels) will work. The thesis begins by critically examining these, arguing that the dominant political economy framework in which they are embedded, precludes real and effective alternatives.Through the prism of the South African coal and electricity sectors, the thesis is able to demonstrate some key issues relevant to global warming, such as class, power, accumulation and the metabolic rift. South Africa was chosen as it represents a microcosm of the global capitalist economy. It also reveals the contradictions of being on the front line, both in facing the consequences of global warming and in exacerbating its causes. The coal and electricity sectors provide a snapshot of conflicting class interests, of the power and pervasiveness of the capitalist system and the relevance of these to global warming.In light of the South African analysis, the thesis argues for the importance of explicit and critical theory as a framework for understanding the world and providing a basis for social change. Critical theory is the dominant framework for political economy. It enables an ecological critique of capitalism, drawing on the historical materialism of Marxism, arguing that the imperatives of capitalism’s unrestrained exploitation of the ecology and society are based in the particular social relations of production. These in turn give rise to the metabolic rift, global warming and a myriad of other symptoms of the crises of capitalism.It is argued that the problems of global warming cannot be solved through capitalism. This means different economic structures will need to be established. The thesis concludes by setting out the principles upon which to build future societies. These are based within the constraints of first, humans’ physical needs for survival; second, the biosphere’s capabilities; and third, the harmonious and restorative relations between humans and nature. While the purpose is not to provide a comprehensive blueprint for the future, the thesis also provides examples of where some of these principles are found currently and of where transformative changes have taken place.